The Use of Lactic Acid Bacteria as Ruminant Probiotic Candidates Based on In Vitro Rumen Fermentation Characteristics - Roni Ridwan; Win Ariga Bungsu; Wulansih Dwi Astuti; Rohmatussolihat Rohmatussolihat; Nurul Fitri Sari; Rusli Fidriyanto; Anuraga Jayanegara; Indah Wijayanti; Yantyati Widyastuti (Buletin Peternakan, 2018)
This research was conducted to select, to identify LAB isolates and to investigate the effects of the LAB as probiotics candidate in the rumen fermentation. Nine isolates exhibited the potency as candidate probiotics for cattle. The experiment was arranged in randomized block design with ten treatments and three different times of in vitro as a block. The substrate consisted of 70% forage and 30% concentrate proportion. The substrate was incubated at 39oC using serum bottle of 100 ml capacity for fermentation. Approximately 0.75 g of substrates was put inside the serum bottle glass and filled with 73 ml of buffered rumen fluid and 2 ml of LAB inoculant. Gas production was measured every 2, 4, 6, 8, 10, 12, 24, 48 and 72 h of the incubation period. Gas production kinetic was estimated by the Ørskov’s equation. The LAB with the highest gas production, as probiotics candidate, were identified using partial 16S rDNA sequence. The results of this research indicated that nine LAB produced high gas production in the range of 193-198 ml compare to that of control (173 ml). The addition of LAB in rumen fermentation resulted in digestibility 65-75%, organic matter digestibility 51-73%, and 6.67-6.68 pH. Based on the molecular identification, 8 isolates are Lactobacillus plantarum and 1 of uncultured bacteria. The LAB strain 32 L. plantarum showed the best for a ruminant probiotic candidate based on the in vitro rumen fermentation characteristic.